Backbone assignment of E. coli NfsB and the effects of addition of the cofactor analogue nicotinic acid - Hyde, Eva I. (Biomol NMR Assign, 2021)
E. coli nitroreductase NfsB (also called NfnB) has been studied extensively, largely due to its potential for cancer gene therapy. A homodimeric flavoprotein of 216 residues, it catalyses the reduction of nitroaromatics to cytotoxic hydroxylamines by NADH and NADPH and also the reduction of quinones to hydroxyquinones. Its role in vivo is not known but it is postulated to be involved in reducing oxidative stress. The crystal structures of the wild type protein and several homologues have been determined in the absence and presence of ligands, including nicotinate as a mimic of the headpiece of the nicotinamide cofactors. There is little effect on the overall structure of the protein on binding ligands, but, from the B factors, there appears to be a decrease in mobility of 2 helices near the active site. As a first step towards examining the dynamics of the protein in solution with and without ligand, we have assigned the backbone (13)C, (15)N, and (1)H(N) resonances of NfsB and examined the effect of the binding of nicotinate on the amide (15)N, and (1)H(N) shifts.